KARAKTERISASI LEMPUNG ALAM DESA GEMA TERAKTIFASI FISIKA - Yanti, Pepi Helza; Muhktar, Akmal (Sam Ratulangi University, 2015)
The characterization of Gema natural clay with thermal activation have been done. Chemical composition of natural clay (NC) were analyzed using XRF technique. The main composition of natural clay were SiO2 65,69 % ; Al2O3 ;24,62 % K2O 4,01 % ; Fe2O3 ; 2,62 % and several oxides of trivial amount. Natural clay was also characterized with XRD instrument to examine the phases or minerals of natural clay, and the results revealed that natural clay consist of quarz, montmorilonite and kaolinite. XRD analysis was also used to determine the possible crystal phase changes of the activated natural clay (ANC) after calcinating with different temperatures (500, 600 and 700oC). The XRD patterns showed there were no changes of minerals type. To learn the effects of thermal activation on the specific surface area were carried out with methylene blue adsorption method. The result proved that specific surface area increased after thermal activation. The specific surface area of activated natural clay (ANC) at 500, 600 and 700oC were 24,2330 m2/g; 40,3006 m2/g and 47,5300 m2/g , respectively. Meanwhile for natural clay the specific surface area was only 17,0857 m2/g. ANC at 700oC was used to analyze the capacity of adsoption to methanil yellow, because adsorptive capacity of an adsorbent is directly linked to its physicochemical properties such asspecific surface area. The examination of adsorbtion with 0,05 mass of ANC and 100 ppm of methanil yellow was 7,12% higher that NC was only 5,38% with same of condition reaction.Telah dilakukan karakterisasi lempung alam Gema melalui temal aktivasi. Komposisi kimia lempung alam (LA) dianalisis menggunakan XRF. Komposisi utama LA adalah SiO2 65,69 % ; Al2O3 ;24,62 % K2O 4,01 % ; Fe2O3 ; 2,62 % dan beberapa senyawa lain dalam jumlah kecil. LA dikarakterisasi menggunakan XRD untuk menentukan jenis mineral yang terdapat pada LA dan hasilnya menunjukkan bahwa LA terdiri atas kuarsa, monmorilinit dan kaolinit. Analisis XRD juga digunakan untuk mengidentifikasikan kemungkinan perubahan fasa LA teraktivasi setelah dikalsinasi (LAK) pada temperatur berbeda (500, 600 dan 700oC). Hasil difraktogram XRD menunjukkan tidak ada perubahan pada jenis mineral lempung. Untuk mempelajari pengaruh aktivasi fisika pada luas permukaan lempung, dilakukan pengujian dengan mengggunakan metode adsorbsi metilen biru. Hasil analisis menunjukkan luas permukaan meningkat setelah termal aktivasi yaitu LAK 500, 600 and 700oC adalah 24,2330m2/g; 40,3006 m2/g dan 47,5300 m2/g. LAK 700oC, digunakan untuk analisis kemampuan daya serap terhadap methanil yellow, karena kapasitas penyerapan dari suatu adsorben berhubungan dengan sifat fisikakimianya seperti luas permukaan. Dari hasil penelitian, diperoleh daya serap optimum LAK 700oC pada 0,05 gram massa adsorben yang dikontakkan dengan 100 ppm methanil yellow adalah 7,12% lebih besar dari LA =5,38% pada kondisi reaksi yang sama.